\(Ta \) \(có : 1 / x - 10x / y = \)\(2\)
\(\Rightarrow\)\(( y - 10x ) / xy = 2 ( Quy đồng )\)
\(\Rightarrow\)\(y - 10x = 2xy\)
\(\Rightarrow\)\(y - 10x - 2xy = 0\)
\(\Rightarrow\)\(( y - 2xy ) - 10x = 5- 5\)
\(\Rightarrow\)\(y. ( 1 - 2x ) - 10x + 5 = 5\)
\(\Rightarrow\)\(y. ( 1 - 2x ) + ( 5 - 10x )= 5\)
\(\Rightarrow\)\(y. ( 1 - 2x ) + 5. ( 1 - 2x ) = 5\)
\(\Rightarrow\)\(( 1 - 2x )( y + 5 )=5\)
\(1 -2x\) | \(- 1\) | \(-5\) | \(1\) | \(5\) |
\(y +5\) | \(-5 \) | \(- 1\) | \(5\) | \(1\) |
\(x\) | \(1\) | \(3\) | \(0\) | \(- 2\) |
\(y\) | \(- 10\) | \(-6\) | \(0\) | \(- 4\) |
\(Vậy : ...............\)